The big back book tips & tricks for therapists - Johnson, Jane, 1965- (Thieme, 2016)
For any therapist who has been challenged by a client complaining of pain or stiffness in the neck or back, The Big Back Book: Tips & Tricks for Therapists is packed with ideas and suggestions for the assessment, treatment, and aftercare of the spine. The author shares tips gathered from many years of experience as a physical therapist and massage therapist, providing step-by-step guidance on everything from testing range of motion and documenting findings, to locating specific muscles and vertebrae, to identifying the source of pain and managing posture and muscle tone issues. With a clear an.